How to do human-subjects research if you do not have an institutional review board. - Rice TW (Respiratory Care, 2008)
Biomedical research with human subjects has expanded outside of traditional medical centers and hospitals into other health care entities, such as rehabilitation facilities, free-standing out-patient treatment centers, and even home-health agencies. Regardless of the location, federal regulations mandate that all human-subjects research must be overseen by an institutional review board (IRB) or ethics committee to ensure the research abides by the Code of Federal Regulations. Consequently, all human-subjects research must be reviewed and approved by an IRB prior to initiation of any research procedures. Unfortunately, many of these nontraditional research facilities do not have easy access to an IRB. This does not render such research exempt from federal oversight. Clinicians at these facilities have viable options for obtaining IRB approval and legally conducting such research. This paper outlines the availalbe options and their pros and cons.